The Legality of Providing Legal Aid to Perpetrators of the Crime of Murder in the Perspective of the Theory of Dignified Justice - Safi’i, Muhlis (Faculty of Law Universitas Negeri Semarang, 2021)
The Unitary State of the Republic of Indonesia is a state of law. In accordance with Article 1 paragraph (3) of the 1945 Constitution (UUD 1945). As a state of law, Indonesia must guarantee the rights of its citizens to equality and guarantees of justice, including human rights. As stated by Salim, quoting Fredrich Julius Stahl, that the main element of a state based on law is the protection, as well as the recognition of Human Rights (HAM), and upholding dignified justice. Also in Article 28D paragraph (1) of the 1945 Constitution (UUD 1945) reads: